De hervormde kerk te Britsum. Een verzwegen kerk onderzocht en gewaardeerd (Bulletin KNOB, 2000)
The Dutch Reformed church of Britsum is situated at the highest point of the characteristic Frisian terp village Britsum, some 12 kilometres to the north of Leeuwarden. The village of Britsum occurs early on in history as ‘Bruggenheim’ in the property registers of the abbey of Fulda. As the source material of the church is scarce, we will have to rely on research of the building itself tor the reconstruction of its building history.The church is of the hall-church type, as customary for Frisian village churches, with as special element the reduced western block, consisting of a tower with flanking adjacent spaces provided with a floor. Research proved that this western block is among the early examples of brick architecture, with a Romanesque detail probably dating from the period l180-1190. The ribless dome vaults of the ground floor were built somewhat later, in the 13th century. Originally. the western block was not vaulted.The greater part of the superstructure of the tower was renovated in the 17th and 18th centuries. Traces of older roof connections at the eastern side of the tower indicate that the present nave was preceded by an older (possibly tuff) hall-nave. The present hall-nave, also completely built of brick, with a choir with slightly recessed semicircular apse, is vaulted with early Romanesque-Gothic domes with sturdy round ribs. In each dome the ribs form a mutually divergent pattern. The course of the ribs and the star patterns and circles in the cresting of the vaults are still somewhat clumsily executed, which indicates an early date. Consequently, the type of vault, the construction and the rib patterns show similarities with the vaults of chiefly 13th century churches in e.g. Groningen and German East Friesland.Because of the construction of this vaulted nave the original circular-arched openings in the eastern front of the western block had to be closed. Nave and western block clearly do not belong together. In the northern wall of the nave and the chevet the remainder of the original, small windows with slightly pointed arches became visible.Furthermore, under the present wall-arches the cut-off pointed-arch shapes of an older vaulting phase came to light in the nave, directly above the old windows. It is not clear whether the vaults belonging to these arches were actually executed or whether the plans for the final vaulting were changed. The research appears to point to the second option, since the masonry of the nave-walls above the older wall-arches continues undisturbedly. It is quite likely that the hall-nave and choir were executed between 1240 and 1250 and the vaulting around 1260 at the latest.The later closed-off, older doorways found in the western bay may still be the original northern and southern doorways, but in view of their protracted circular-arch closings they must at least have been rebuilt (widened). The present, probably 19th-century northern and southern entrance are to the west of these old doorways. In the 15th century large pointed arch windows were applied in the southern wall of the nave and the southern chevet. Possibly this operation was related to the rebuilding of the doorways and the replacement of the first roof by the present oak roof construction dated directly after 1465 by means of dendrochronological research.After several smaller renovations in the 17th and 18th centuries a fundamental operation took place in 1875, when the church acquired an entirely new neo-Gothic exterior clamp in smooth red brick with accents in yellow stone. In 1895 the present outfit of the reduced western block and tower in brick (possibly built earlier) appears, varied with plastered details in an eclectic form language. Recently the restoration of the exterior took place (1992-93) and of the interior with paintings.